The Measurement of Corporate Portfolio Strategy: Analysis of the Content Validity of Related Diversification Indexes - ROBINS, James Arthur (Institutional Knowledge at Singapore Management University, 2003)
Measures developed for the analysis of corporate diversification have become fundamental to a broad range of strategy research. This paper examines the content validity of the two most widely used continuous measures of related diversification--the related component of the entropy index and the concentric index--and raises fundamental questions about their validity as indicators of portfolio relatedness. These questions are not driven by the use of SIC data for estimation of the indexes; they involve validity problems intrinsic to the construction of the measures. The related component of entropy and the concentric index are sensitive to features of corporate portfolio composition that may not be directly linked to portfolio relatedness. These sensitivities can create important ambiguities in strategy research.